2010
DOI: 10.1002/jmv.21730
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of complete genome sequences of swine hepatitis E virus and possible risk factors for transmission of HEV to humans in Korea

Abstract: The hepatitis E virus (HEV) is an emerging zoonotic agent, for which pigs are the most important reservoir. Complete genome sequences of two swine HEV strains, designated swKOR-1 and swKOR-2, were determined via RT-PCR and RACE-PCR. The strains contained genomes composed of 7,222- and 7,221-bp excluding the poly(A) tails, respectively. The swKOR-1 and swKOR-2 strains were classified into subtype 3a of genotype 3 via phylogenetic analysis. These strains formed a distinctive cluster in the phylogenetic tree with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 51 publications
4
52
2
Order By: Relevance
“…The large variation observed for oysters was due to a high value in July (allometric coefficient of 22). For clams, the allometric coefficients in January and March (10 and 9) were lower than those obtained in the 3 other experiments (14,16,18). For the 2 other species, low variability was observed.…”
Section: Conditions For the Bioaccumulation Experimentsmentioning
confidence: 69%
See 2 more Smart Citations
“…The large variation observed for oysters was due to a high value in July (allometric coefficient of 22). For clams, the allometric coefficients in January and March (10 and 9) were lower than those obtained in the 3 other experiments (14,16,18). For the 2 other species, low variability was observed.…”
Section: Conditions For the Bioaccumulation Experimentsmentioning
confidence: 69%
“…For example, HEV was detected in Italian mussels that were being utilized as bioindicators of marine pollution (11) and in marketplace mussels in Spain (49). In Thailand, none of 213 samples analyzed were found to be positive for HEV (50), and in Korea, about 9% of 161 oyster samples were positive (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is probably why eating seafood has been found to be associated with the presence of anti-HEV IgG and why the HEV genome has been identified in oysters-they are grown mainly in estuaries. (40) This could well explain why we found that eating oysters was linked to the presence of IgG.…”
Section: Mansuy Gallian Et Al Hepatology April 2016mentioning
confidence: 77%
“…Therefore, a number of epidemiological studies have been conducted on domestic and wild swine populations to determine the prevalence of HEV infection worldwide (de Deus et al, 2008;Kaba et al, 2010;Martelli et al, 2008;Rueter et al, 2009;Schielke et al, 2009, Takahashi et al, 2014. Previous serological studies performed on human, pig, and cat populations in Korea reported an 18%, 15%, and 8.1% prevalence of anti-HEV antibodies (Choi et al, 2003;Song et al, 2010). Moreover, anti-HEV antibodies were detected in 14 of 64 zoo animal species at different ratios (Song et al, 2013).…”
Section: Introductionmentioning
confidence: 99%